2019
DOI: 10.1007/s10680-019-09527-y
|View full text |Cite
|
Sign up to set email alerts
|

Natives’ and Immigrants’ Gender Preferences for Children in Germany

Abstract: Little research has been conducted yet investigating gender preferences among immigrant parents in Western host countries. We add further empirical evidence to this sparse literature by analyzing pooled micro-census data for the years 2005-2013 from Germany. Next to updating earlier findings on the native population, we assess parental gender preferences in two large and culturally distinct groups of immigrants in Germany, namely those with Turkish and Polish origins. Our analysis indicates both daughter and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…Evidence from the US and Canada, as well as for Finnish-born immigrants to Sweden, indicates cultural persistence (Al Harahsheh 2011;Almond et al 2013), whereas other US evidence as well as findings from Israel indicate acculturation (Okun 1996;Ost and Dziadula 2016). As previously mentioned, newer studies from Sweden (Mussino et al 2019) and Germany (Carol and Hank 2019) also provide support for cultural persistence, although the first found that arrival in childhood and whether the father of the second-born child was Swedish were associated with acculturation. Our findings are therefore in line with those found in the existing literature on sex preferences.…”
Section: Cultural Assimilation: Papers 1 Andmentioning
confidence: 93%
See 1 more Smart Citation
“…Evidence from the US and Canada, as well as for Finnish-born immigrants to Sweden, indicates cultural persistence (Al Harahsheh 2011;Almond et al 2013), whereas other US evidence as well as findings from Israel indicate acculturation (Okun 1996;Ost and Dziadula 2016). As previously mentioned, newer studies from Sweden (Mussino et al 2019) and Germany (Carol and Hank 2019) also provide support for cultural persistence, although the first found that arrival in childhood and whether the father of the second-born child was Swedish were associated with acculturation. Our findings are therefore in line with those found in the existing literature on sex preferences.…”
Section: Cultural Assimilation: Papers 1 Andmentioning
confidence: 93%
“…Their evidence therefore supports the importance of cultural persistence but is also consistent with some forms of adaption or acculturation. Carol and Hank (2019)…”
Section: Summary Of the First Paper And New Research From The Post-pumentioning
confidence: 99%
“…Finally, our use of survey rather than census data, while limiting the number of observations, allows us to incorporate several interesting control variables that are not available in the German census but remain relevant when examining gender preferences. These latter two contributions allow our analysis to further expand the work of Carol and Hank (2019).…”
Section: Introductionmentioning
confidence: 90%
“…Nevertheless, there is scant research on this phenomenon among immigrants in Germany. An important exception is the research conducted by Carol and Hank (2019) comparing German native and immigrant (Turkish and Polish) parental gender preferences for their offspring. Our paper seeks to add to this line of research by comparing parental gender preferences for offspring between native German women and immigrant Turkish women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation